2018
DOI: 10.3389/fpsyg.2018.01977
|View full text |Cite
|
Sign up to set email alerts
|

Effective Educational Strategies to Promote Life-Long Musical Investment: Perceptions of Educators

Abstract: While research has broadly considered the wide-ranging intellectual, social, personal, and physical benefits of active musical participation across the lifespan, there is little research that explores how music educators work to promote participant investment inside school and beyond. The present research, therefore, aimed to investigate the practices employed by leading music educators within a range of cultural and pedagogical contexts that facilitate investment toward life-long engagement in music. Intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Relatedly, much of the relevant work can be challenged on the grounds of a lack of theoretical grounding (Clift and Hancox, 2010). Recently, researchers (e.g., Küpers et al, 2014; Evans, 2015; Krause and Davidson, 2018) have suggested the utility of Self-Determination Theory as a framework to consider musical participation and well-being. Self-Determination Theory has been applied to a wide range of social psychological behaviors, spanning health, education, and social relationships, and is supported by a growing body of research (Evans, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, much of the relevant work can be challenged on the grounds of a lack of theoretical grounding (Clift and Hancox, 2010). Recently, researchers (e.g., Küpers et al, 2014; Evans, 2015; Krause and Davidson, 2018) have suggested the utility of Self-Determination Theory as a framework to consider musical participation and well-being. Self-Determination Theory has been applied to a wide range of social psychological behaviors, spanning health, education, and social relationships, and is supported by a growing body of research (Evans, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, when it comes to teaching blind students at the beginner level, educators encounter a myriad of unique challenges that require innovative strategies and a nuanced understanding of pedagogy. This study delves into the intricate landscape of challenges faced by teachers in instructing blind students in piano at the beginner level, aiming to comprehensively explore and analyze these challenges while also uncovering effective strategies to enhance the learning experiences of visually impaired learners [1,2,3,4] . The background of this research stems from the increasing recognition of the importance of inclusive education across various domains, including music education.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of music education, the integration of diverse cultural elements and teaching methodologies has become increasingly significant in fostering a comprehensive and enriching learning experience. One such approach that has garnered attention is the integration of Chinese Nationalized Piano Education into modern music pedagogy [1][2][3][4][5][6] . This integration aims to combine the rich heritage and unique teaching methods of Chinese piano education with the contemporary practices of music instruction, creating a fusion that enhances students' musical understanding and appreciation [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%